2014
DOI: 10.1186/1471-2407-14-920
|View full text |Cite
|
Sign up to set email alerts
|

Human hematopoietic signal peptide-containing secreted 1 (hHSS1) modulates genes and pathways in glioma: implications for the regulation of tumorigenicity and angiogenesis

Abstract: BackgroundHuman Hematopoietic Signal peptide-containing Secreted 1 (hHSS1) is a truly novel protein, defining a new class of secreted factors. We have previously reported that ectopic overexpression of hHSS1 has a negative modulatory effect on cell proliferation and tumorigenesis in glioblastoma model systems. Here we have used microarray analysis, screened glioblastoma samples in The Cancer Genome Atlas (TCGA), and studied the effects of hHSS1 on glioma-derived cells and endothelial cells to elucidate the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…EMC6 knockdown increases glioblastoma cell proliferation, whereas overexpression slows proliferation, inhibits invasiveness and enhances chemotherapeutic sensitivityall properties consistent with some role in tumour suppression (Shen et al, 2016). EMC10-2 overexpression also inhibits glioma-induced cell cycle progression and invasion (Junes-Gill et al, 2014). EMC6 overexpression improved survival in a glioma xenograft mouse model, attributed to induction of autophagy and PI3K-Akt-mTOR signalling pathway downregulation (Shen et al, 2016).…”
Section: Cancermentioning
confidence: 60%
See 1 more Smart Citation
“…EMC6 knockdown increases glioblastoma cell proliferation, whereas overexpression slows proliferation, inhibits invasiveness and enhances chemotherapeutic sensitivityall properties consistent with some role in tumour suppression (Shen et al, 2016). EMC10-2 overexpression also inhibits glioma-induced cell cycle progression and invasion (Junes-Gill et al, 2014). EMC6 overexpression improved survival in a glioma xenograft mouse model, attributed to induction of autophagy and PI3K-Akt-mTOR signalling pathway downregulation (Shen et al, 2016).…”
Section: Cancermentioning
confidence: 60%
“…EMC10 pleiotropy was first hinted at by the discovery that hematopoietic stem cells express two splice variants. In constrast to full-length TMD-containing EMC10, EMC10-2 (also known as HSS1) lacks a discernible TMD and is secreted into the extracellular space (Junes-Gill et al, 2011;Junes-Gill et al, 2014). EMC10-2 is biologically active and mediates a range of cellline-dependent effects.…”
Section: Moonlighting Emc Subunitsmentioning
confidence: 99%
“…Table 1 Recently discovered pro-and anti-angiogenesis factors Pro-angiogenesis TGLI1 [63], H19 [51], C/EBPbeta [14], MCSF [15], annexin A2 [39], CXCR4 [66], Oct-3/4 [16], miR-31 [50], miR-148a, HSP47 [38] Anti-angiogenesis hHSS1 [29], NNC55-0396 [30], TTAC-0001 [67], calpastatin [68], miR-137 [65], EZH2 [65], BMP7v [31], PDCD10 [32], JSI-124 [33] Brain Tumor Pathol…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, targeted anti-angiogenic therapy with Avastin, a monoclonal antibody against vascular endothelial growth factor, could induce temporary remission of the cancer on MRI, but does not effectively prolong the overall survival time [28]. Overexpressing human hematopoietic signal peptidecontaining secreted 1 (hHSS1), a novel protein defined as a new class of secreted factors, could apparently inhibit tube formation in GBM and hence significantly decrease the GBM-induced cell cycle progression, migration, invasion and angiogenesis [29]. NNC55-0396, a T-type Ca 2?…”
Section: Angiogenesis In Gbm and Anti-angiogenic Therapiesmentioning
confidence: 99%
“…18 In an in vitro study, EMC10 was suggested as a potential therapeutic target for malignant glioblastoma after being found to exert cell proliferation inhibition, invasion, angiogenesis in endothelial cells, and cell migration in glioma cell lines. 19,20 In schizophrenia mouse models, reduced Mirta22 (human EMC10 ortholog) levels completely rescued the dendritic deficits and spine formation at the hippocampal pyramidal neurons, thus suggesting a key role in neuronal dendrites and spine development. 21 Furthermore, studies revealed that knockout mouse (emc10 −/− ) showed effects on their behavior (hyperactivity, abnormal gait, and abnormal vocalization), decreased bone mineral content, persistence of hyaloid vascular system, cardiovascular issues (decreased heart rate), deceased corpuscular volume in females, thrombocytopenia, metabolic effects, and infertility phenotypes in males (MGI: 5548589).…”
Section: Discussionmentioning
confidence: 99%